2013
DOI: 10.3389/fpsyg.2013.00287
|View full text |Cite
|
Sign up to set email alerts
|

Beyond perceptual load and dilution: a review of the role of working memory in selective attention

Abstract: The perceptual load and dilution models differ fundamentally in terms of the proposed mechanism underlying variation in distractibility during different perceptual conditions. However, both models predict that distracting information can be processed beyond perceptual processing under certain conditions, a prediction that is well-supported by the literature. Load theory proposes that in such cases, where perceptual task aspects do not allow for sufficient attentional selectivity, the maintenance of task-releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 89 publications
1
54
0
Order By: Relevance
“…This model makes opposite predictions as to the effects of perceptual load and cognitive load on task-irrelevant information processing. Numerous studies, using behavioral and neuroimaging measures, have shown that indeed greater perceptual demand on a visual task is associated with reduced interference and successful selective attention, whereas higher demand on cognitive control (e.g., working memory, dual task) is associated with increased processing of irrelevant information (de Fockert, 2013; de Fockert et al, 2001; Kelley and Lavie, 2011; Rees et al, 1997; Schwartz et al, 2005; Xu et al, 2011). The effects of perceptual demand and working memory load on sensory processing of task-irrelevant visual distractors were observed as early as primary visual cortex (area V1) (Bahrami et al, 2007; Kelley and Lavie, 2011; Schwartz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This model makes opposite predictions as to the effects of perceptual load and cognitive load on task-irrelevant information processing. Numerous studies, using behavioral and neuroimaging measures, have shown that indeed greater perceptual demand on a visual task is associated with reduced interference and successful selective attention, whereas higher demand on cognitive control (e.g., working memory, dual task) is associated with increased processing of irrelevant information (de Fockert, 2013; de Fockert et al, 2001; Kelley and Lavie, 2011; Rees et al, 1997; Schwartz et al, 2005; Xu et al, 2011). The effects of perceptual demand and working memory load on sensory processing of task-irrelevant visual distractors were observed as early as primary visual cortex (area V1) (Bahrami et al, 2007; Kelley and Lavie, 2011; Schwartz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This account has received substantial support from studies on vision (reviewed in de Fockert, 2013;Lavie, 2005) and audition (Alain & Izenberg, 2003;Conway, Cowan, & Bunting, 2001;Dalton, Santangelo, & Spence, 2009;Fairnie, Moore, & Remington, 2016;Muller-Gass & Schröger, 2007; but see Murphy, Fraenkel, & Dalton, 2013), and from studies probing load theory for crossmodal attention (Berman & Colby, 2002;Brand-D'Abrescia & Lavie, 2008;Jacoby, Hall, & Mattingley, 2012;Macdonald & Lavie, 2011;Molloy, Griffiths, Chait, & Lavie, 2015;Raveh & Lavie, 2015; but see Tellinghuisen & Nowak, 2003). Interestingly, and at variance with load theory, several studies have suggested that faces present a special case, in the sense that they may recruit a domain-specific capacity-limited system (Neumann, Mohamed, & Schweinberger, 2011;Neumann & Schweinberger, 2008).…”
mentioning
confidence: 98%
“…According to load theory (Lavie et al, 2004), higher working memory load impairs selective attention and increases distractor interference. Thus, when cognitive demands are low, interference is reduced due to more available resources to concurrently maintain task performance and process distracting stimuli (for review see: de Fockert, 2013). Several neuroimaging studies have highlighted the critical role of regions within the prefrontal cortex in the control of selective attention to task-specific stimuli (Corbetta & Shulman, 2002; de Fockert et al, 2004; de Fockert & Theeuwes, 2012; Hopfinger et al, 2001).…”
mentioning
confidence: 99%